Measuring Career Well-Being on Working Mothers: Adaptation of Well-Being at Work Scale - Hilwa Anwar; Fendy Suhariadi; Fajrianthi Fajrianthi (Journal of Educational, Health and Community Psychology, 2020)
AbstractÂ This research aimed to conduct the adaptation and validation of the Well-Being at Work Scale (WBWS) in order to ready it for implementation as the instrument to measure career well-being on working mothers as respondents in Indonesia. The career well-being approach was based on the concept of general well-being which included affective and cognitive components. The respondents were mothers working full-time in the formal sector and had fulfilled the requirement of several pre-determined criteria. The collected research data was analyzed with the confirmatory factor analysis in order to obtain instrument reliability and validity. Based on the analysis, results were obtained that the WBWS model adaptated had fulfilled the goodness-of-fit criteria, meaning that there was compatibility between the developed model and the empirical data. Furthermore, this research was hoped to provide contribution in the measurement and development of research of career well-being on working mothers.Â